Determining the Best Web Designer Using the SMARTER Method (Case Study: Website Development Service Provider) - Patria, Lintang; Sitompul, Bernad J. D.; Marbun, Nasib (CV. Media Digital Publikasi Indonesia, 2024)
This research aims to solve the problem of determining the best Web Designer objectively for website development service business activists. In this research, the author offers SMARTER as a decision support system method to produce a ranking of the best Web Designer alternatives to be selected by decision makers. The alternatives selected as the best Web Designer in this study consist of 5 candidates (AX1, AX2, AX3, AX4, and AX5). The criteria used in the process of determining the best Web Designer in this study are communication, ability to design websites, discipline, and loyalty. The results of the application of the SMARTER method in this study recommend alternative AX3 to the decision maker to be selected as the best web designer who is entitled to a reward